Environmental impact of cement production and Solutions: A review - Nabilla, Mohamad; Khairunisa, Muthusamy; Rahimah, Embong; Andri, Kusbiantoro; Mohd Hanafi, Hashim (Elsevier Ltd, 2022)
This paper reviews the impact of cement industry towards the global environment and solutions to the problem. The increasing harvesting of raw materials for mounting cement manufacturing causes reduction in quantity of the non-renewable resources such as limestone. The activities linked to harvesting of the resources from natural surroundings, damages the green landscape which is the habitat of flora and fauna exposing to the risk of ecological imbalance. The continuous reaping of these precious resources, exposes it to the risk of depletion in future. Furthermore, the raw materials processing phases in the factory releases dust, noises, greenhouse gases especially carbon dioxide that contaminates the environment and aggravates the climate change. These uninvited environmental issues cause distress to the lifestyle of mankind. Therefore, enhancing the manufacturing technology of cement plant for cleaner production is one of the resolutions to this issue. Approach of using industrial waste as supplementary cementitious material or cement free concrete also would reduce dependency on cement demand. Success in utilizing other alternative material which production consumes lesser natural resources, economic and has lesser harm to the nature to act as binder in concrete would contribute to sustainable and healthier environment for future generation.